Iron-carbon material enhanced electrokinetic remediation of PCBs-contaminated soil. (1st December 2021) - Song, Yan; Lei, Cheng; Yang, Kun; Lin, Daohui
Abstract: The high toxicity and persistence of polychlorinated biphenyls (PCBs) in the environment demands the development of effective remediation for PCBs-contaminated soils. In this study, electrokinetic (EK) remediation integrated with iron-carbon material (Fe/C) was established and used to remediate PCB28 (1 mg kg −1 ) contaminated soil under a voltage gradient of 1 V cm −1 . Effects of Fe/C dosage, soil type, and remediation time were investigated. The operational condition was optimized as 4 g kg −1 Fe/C, yellow soil, and 14 d-remediation, achieving PCB28 removal efficiency of 58.6 ± 8.8% and energy utilization efficiency of 146.5. Introduction of EK-Fe/C did not significantly affect soil properties except for slight soil moisture content increase and total Fe content loss. Soil electrical conductivity exhibited an increasing trend from anode to cathode attributed to EK-induced electromigration and electroosmosis. EK accelerated the corrosion and consumption of reactive Fe 0 /Fe3 C in Fe/C by generating acid condition. Fe/C in turn effectively prevented EK-induced soil acidification and maintained soil neutral to weak alkaline condition. A synergistic effect between EK and Fe/C was revealed by the order of PCB28 removal efficiency-EK-Fe/C (58.6 ± 8.8%) > EK (37.7 ± 1.6%) > Fe/C (6.8 ± 5.0%). This could be primarily attributed to EK and Fe/C enhanced Fenton reaction, where EK promoted Fe/C dissolution and H2 O2 generation. In addition to oxidation by Fenton reaction generated ·OH, EK-mediated electrochemical oxidation, Fe/C-induced reduction and migration of Fe/C adsorbed PCBs were all significant contributors to PCB28 removal in the EK-Fe/C system. These findings suggest that the combination of EK and Fe/C is a promising technology for remediation of organics-contaminated soil. Graphical abstract: Image 1 Highlights: The combination of EK and Fe/C achieved 58.6% PCBs removal from soil in 14 days. Soil properties were not significantly affected by EK-Fe/C remediation. EK-induced acid condition promoted the corrosion of Fe 0 /Fe3 C in Fe/C. EK led to the migration of Fe/C adsorbed PCBs from anode to cathode. EK and Fe/C synergistically enhanced Fenton reaction to improve PCBs removal. Abstract : EK and Fe/C synergistically remediated PCBs-contaminated soils.